The Growth Role of Artificial Intelligence (AI) in Strategy Management in UMKM - Verdiana, Yuni Qoriah; Fachir, Zidane Azrulludin; A’dhom, Mohammad Ghouzul (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2023)
This study aims to investigate the growing role of Artificial Intelligence (AI) in the strategic management of Micro, Small, and Medium Enterprises (UMKM). The use of AI in UMKM can provide significant operational efficiency. The research method used is a literature study with bibliometric analysis. The results showed that the use of AI has excellent potential benefits for UMKM in the future. In addition to increasing efficiency, the application of AI can also encourage the liveliness and competitiveness of UMKM in the digital era. With the help of AI, UMKM can adapt quickly to technological developments and develop their business processes more effectively.